In 2024, the amyloid-cascade-hypothesis still remains a working hypothesis, no less but certainly no more - Behl, Christian (Frontiers in Aging Neuroscience, 2024)
The amyloid-cascade-hypothesis of the pathogenesis of Alzheimer’s disease (AD) was introduced 32 years ago, in 1992. From early on, this clear and straight forward hypothesis received a lot of attention, but also a lot of substantial criticism. Foremost, there have always been massive doubts that a complex age-associated disorder of the most intricate organ of the human body, the brain, can be explained by a linear, one-dimensional cause-and-effect model. The amyloid-cascade defines the generation, aggregation, and deposition of the amyloid beta peptide as the central pathogenic mechanism in AD, as the ultimate trigger of the disease, and, consequently, as the key pharmacological target. Certainly, the original 1992 version of this hypothesis has been refined by various means, and the ‘formulating fathers’ followed up with a few reappraisals and partly very open reflections in 2002, 2006, 2009, and 2016. However, up until today, for the supporters of this hypothesis, the central and initial steps of the cascade are believed to be driven by amyloid beta—even if now displayed somewhat more elaborate. In light of the recently published clinical results achieved with anti-amyloid antibodies, the controversy in the field about (1) the clinical meaningfulness of this approach, (2) the significance of clearance of the amyloid beta peptide, and last but not least (3) the relevance of the amyloid-cascade-hypothesis is gaining momentum. This review addresses the interesting manifestation of the amyloid-cascade-hypothesis as well as its ups and downs over the decades.